COMPARATIVE ESTIMATION OF AUDIT EVIDENCES EFFICIENCY WHEN GROUNDING THE DECISION OF AUDITOR PROCEDURES MODIFICATION - V. A. Yakimova (Russian Journal of Economics and Law)
The article views the notion of audit evidences efficiency and proposes the mathematical model based on expert estimations and fuzzy-set theory. The proposed model allows to quantitatively estimate and ground the decision on audit procedures modification when it is necessary to get additional or alternative evidence and change the character volume and temporal frameworks of audit procedures.